(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explores the influence of the Yassawi Sufi order, founded by Khoja Ahmad Yassawi, and his devoted disciple Sulayman Boqirgani on the literary development of the Volga region, particularly in Tatar literature. The paper analyzes how themes of divine love, spiritual purification, and social justice expressed in Yassawi’s teachings are reflected in Sulayman Boqirgani’s work and continued in Qul Ali’s epic Qissayi Yusuf. The study highlights the tradition of literary succession within Turkic-Tatar literature.